Value of C- Reactive Protein and White Blood Cells Count in Confirming the Diagnosis of Acute Appendicitis - Mohamed Bellael; Moath Ben Taher (AlQalam Journal of Medical and Applied Sciences, 2024)
Acute appendicitis is one of the most frequent abdominal emergency operations in any surgical ward. The majority of professionals recommend early diagnosis and prompt surgical intervention (appendectomy) to decrease the morbidity and mortality which is associated with late diagnosis and appendicular perforation. A history and clinical examination are frequently utilized to facilitate early diagnosis, which is usually supported by laboratory tests and abdominal and pelvic ultrasound. The aim of our study is to investigate the diagnostic value of white blood cells (WBC) count and C-reactive protein (CRP) in confirming the diagnosis of acute appendicitis in suspected patients. A prospective study was conducted on 100 patients admitted to surgical ward in Alwahda teaching hospital (Derna, Libya) with abdominal pain and suspected to be acute appendicitis. Patients who operated for acute appendicitis (appendectomy) were divided according to their histopathology results into 80 cases with acute appendicitis and 20 with normal appendicitis. The results of histopathology were compared to the preoperative level of CRP & WBC count. A statistically significant increase in CRP and WBC was observed in acute appendicitis patients in comparison with normal appendicitis patients. CRP had a specificity of 65% and sensitivity of 70%, with significance for the prediction of acute appendicitis. WBC had a specificity of 55% and sensitivity of 83%, which is significant for predicting acute appendicitis. Overall, both CRP and WBC provide valuable diagnostic insights, with WBC showing a superior ability to detect true cases of acute appendicitis. However, the moderate specificity of both markers suggests that they have to be used in conjunction with other clinical assessments and diagnostic tools to improve diagnostic precision and reduce false positives. التهاب الزائدة الدودية الحاد هو أحد أكثر العمليات الجراحية الطارئة شيوعًا في البطن في أي جناح جراحي. يوصي غالبية المهنيين بالتشخيص المبكر والتدخل الجراحي السريع (استئصال الزائدة الدودية) لتقليل معدل الإصابة والوفيات المرتبطة بالتشخيص المتأخر وثقب الزائدة الدودية. غالبًا ما يتم استخدام التاريخ والفحص السريري لتسهيل التشخيص المبكر، والذي عادة ما يكون مدعومًا باختبارات معملية وموجات فوق صوتية للبطن والحوض. الهدف من دراستنا هو التحقيق في القيمة التشخيصية لعدد خلايا الدم البيضاء والبروتين التفاعلي سي في تأكيد تشخيص التهاب الزائدة الدودية الحاد لدى المرضى المشتبه بهم. أجريت دراسة مستقبلية على 100 مريض تم إدخالهم إلى جناح الجراحة في مستشفى الوحدة التعليمي (درنة، ليبيا) يعانون من آلام في البطن ويشتبه في إصابتهم بالتهاب الزائدة الدودية الحاد. تم تقسيم المرضى الذين أجريت لهم عملية جراحية لالتهاب الزائدة الدودية الحاد (استئصال الزائدة الدودية) وفقًا لنتائج الفحص النسيجي إلى 80 حالة مصابة بالتهاب الزائدة الدودية الحاد و20 حالة مصابة بالتهاب الزائدة الدودية الطبيعي. تمت مقارنة نتائج الفحص النسيجي بمستوى ما قبل الجراحة لبروتين سي التفاعلي وعدد خلايا الدم البيضاء. لوحظت زيادة ذات دلالة إحصائية في بروتين سي التفاعلي وعدد خلايا الدم البيضاء لدى مرضى التهاب الزائدة الدودية الحاد مقارنة بمرضى التهاب الزائدة الدودية الطبيعي. كان لبروتين سي التفاعلي خصوصية 65% وحساسية 70%، مع أهمية للتنبؤ بالتهاب الزائدة الدودية الحاد. كان لبروتين سي التفاعلي خصوصية 55% وحساسية 83%، وهو أمر مهم للتنبؤ بالتهاب الزائدة الدودية الحاد. بشكل عام، يوفر كل من بروتين سي التفاعلي وعدد خلايا الدم البيضاء رؤى تشخيصية قيمة، حيث يُظهر كل من بروتين سي التفاعلي وعدد خلايا الدم البيضاء قدرة فائقة على اكتشاف الحالات الحقيقية لالتهاب الزائدة الدودية الحاد. ومع ذلك، فإن الخصوصية المعتدلة لكلا العلامتين تشير إلى أنه يجب استخدامهما جنبًا إلى جنب مع التقييمات السريرية الأخرى وأدوات التشخيص لتحسين دقة التشخيص والحد من الإيجابيات الكاذبة